2018
DOI: 10.1101/440412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Sectional and Longitudinal Brain Scans Reveal Accelerated Brain Aging in Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an inflammatory disorder of the central nervous system. By combining longitudinal MRI-based brain morphometry and brain age estimation using machine learning, we tested the hypothesis that MS patients have higher brain age relative to chronological age than healthy controls (HC) and that longitudinal rate of brain aging in MS patients is associated with clinical course.Seventy-six MS patients, 71 % females and mean age 34.8 years (range 21-49) at inclusion, were examined with brain M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several processing steps, such as skull stripping, Talairach transforms, atlas registration as well as spherical surface maps and parcellations are then initialized with common information from the within-subject template, significantly increasing reliability and statistical power (Reuter et al, 2012). Due to the longitudinal stream in FreeSurfer influencing the thickness estimates, and subsequently having an impact on brain age prediction (Høgestøl et al, 2019), both cross-sectional and longitudinal data in the test set were processed with the longitudinal stream. All reconstructions were visually assessed and edited by trained research personnel.…”
Section: Freesurfer Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several processing steps, such as skull stripping, Talairach transforms, atlas registration as well as spherical surface maps and parcellations are then initialized with common information from the within-subject template, significantly increasing reliability and statistical power (Reuter et al, 2012). Due to the longitudinal stream in FreeSurfer influencing the thickness estimates, and subsequently having an impact on brain age prediction (Høgestøl et al, 2019), both cross-sectional and longitudinal data in the test set were processed with the longitudinal stream. All reconstructions were visually assessed and edited by trained research personnel.…”
Section: Freesurfer Processingmentioning
confidence: 99%
“…The difference between the brain-predicted age and an individual's chronological age, also referred to as the brain age gap (BAG), can be used to assess deviations from expected age trajectories, with potential utility in studies of brain disorders and ageing (Cole et al, 2017;. This has clear clinical implications for patient groups, where studies have reported larger brain age gaps in patients with various neurological and psychiatric disorders (Han et al, 2020;Høgestøl et al, 2019;Pardoe et al, 2017;Sone et al, 2019;Tønnesen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A preprint of this manuscript was published at bioRxiv (https://www.biorxiv.org/content/10.1101/440412v1) on October 10th 28 (34).…”
Section: Author’s Notementioning
confidence: 99%
“…Unfortunately, there are currently no symptoms, physical findings, or laboratory tests to accurately diagnose MS [34][35]. For this reason, several methods are used to diagnose MS that include reviewing the patient's medical history [36][37], medical imaging techniques such as MRI [38][39][40], spinal fluid analysis [41][42], and blood tests [43][44]. Currently, MRI modalities are the best non-invasive method used for the diagnosis of MS [45][46][47].…”
Section: Introductionmentioning
confidence: 99%